Progress and Developments in Ionic Liquids 2017
DOI: 10.5772/65924
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ionic Liquids in Protein Folding/Unfolding Studies

Abstract: Ionic liquids (ILs) have emerged as novel solvent medium for several biotechnological processes in vitro. The use of ILs starts from protein extraction to catalysis to folding/ unfolding studies. ILs are becoming the most favorite non-aqueous medium for protein studies due to their unique ionic combinations (cation + anion) and tunable physical properties. In this context, several research results have been published that use of pure or aqueous IL solutions as stabilizer for proteins. Hence, herein, in this ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…ILs have been proposed as green alternatives to conventional organic solvents, which are known to be harmful to the environment. Although it has been shown that certain families of ILs and those that contain long alkyl chains possess increased levels of toxicity and may pose a threat to the environment, suitable design can diminish their toxicity levels. For instance, having short alkyl chains ( n < 4) and polar functional groups are often useful in reducing toxicity. ,, Moreover, research in this area revealed that it is possible to generate ILs which are nontoxic and biodegradable. , Furthermore, ILs which are safe to use in contact with skin have also been found. , The versatility of ILs imparted through the change of the ion constituents and combination is one of their key merits, enabling the possibility to tweak physical properties for various applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ILs have been proposed as green alternatives to conventional organic solvents, which are known to be harmful to the environment. Although it has been shown that certain families of ILs and those that contain long alkyl chains possess increased levels of toxicity and may pose a threat to the environment, suitable design can diminish their toxicity levels. For instance, having short alkyl chains ( n < 4) and polar functional groups are often useful in reducing toxicity. ,, Moreover, research in this area revealed that it is possible to generate ILs which are nontoxic and biodegradable. , Furthermore, ILs which are safe to use in contact with skin have also been found. , The versatility of ILs imparted through the change of the ion constituents and combination is one of their key merits, enabling the possibility to tweak physical properties for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decade, there has been an intense focus on the use of ILs as solvents for biomolecules such as proteins, enzymes, and nucleic acids, such as DNA. , Numerous studies have shown that when ILs are used as media for biomolecules, properties and behavior of the solute are enhanced, as compared to using conventional solvents, such as water or organic solvents. ,,, The review by Patel et al (ref ) gives a comprehensive summary of the application of ILs as solvents for proteins, whereas the review by Sivapragasam et al (ref ) provides an overview of the development in the field of ILs used in combination with biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids, composed of large and asymmetric ions, offer a diverse array of intermolecular interactions with water and the various chemical moieties commonly found on protein surfaces . These versatile liquids have gradually replaced conventional and hazardous organic solvents in applications related to protein stability and tuning enzyme activity, for example. , However, fewer studies have delved into systems involving salt mixtures compared to single-salt solutions …”
Section: Introductionmentioning
confidence: 90%